Analysis of the shape characteristics and nutritional components of Akebia trifoliata in Qinba Mountains - Wang, Min; Guo, Xiaocheng; Song, Junyang (Frontiers in Plant Science, 2022)
Akebia trifoliata (A. trifoliata) is a widely distributed wild vine that has attracted much attention in recent years due to the edible fruit of food and medicinal value. In this paper, the fruits of A. trifoliata, which are derived from Qinling Mountains (12 genotypes) and Bashan Mountains (4 genotypes) and have been artificially domesticated and cultivated for many years, are taken as the research object to study the fruit characteristics and pulp components of 16 genotypes of A. trifoliata. The results show that the pulp of the 16 genotypes contain a variety of nutrients, among which the average contents of total sugar, total acid, vitamin C, soluble solids and starch are 14.68g/100g, 0.14g/100g, 26.40mg/100g, 17.95% and 5.29g/100g. The fruit contains 17 amino acids, including 7 essential amino acids and 4 organic acids. The latter refers to malic acid, lactic acid, citric acid and fumaric acid, the the average contents of which are 1.03g/kg, 3.38g/kg, 0.33g/kg and 0.0149g/kg. Besides, 8 mineral elements in the fruit include 4 macro elements and 4 micro elements. The average contents of the former are potassium (1.83g/kg), calcium (0.23g/kg), phosphorus (0.28g/kg) and magnesium (0.21g/kg), and the average contents of the latter are iron (2.29mg/kg), zinc (2.23mg/kg), copper (1.37mg/kg) and manganese (5.52mg/kg). During the ripening process of A. trifoliata fruit (using HY-9 as the material), the main nutrients in the pulp such as total sugar, soluble solids, starch, amino acids and various mineral elements reach the maximum in stage 3, indicating that stage 3 is the the best edible period of A. trifoliata fruit. Through the assignment analysis and comprehensive evaluation of 9 quality indicators (3 apparent characters and 6 main chemical components) of the fruits of the 16 A. trifoliata genotypes from Qinba Mountains, HY-1, HY-2 and HY-9 were finally screened out as the three superior genotypes. This study aims to provide reference for the development and utilization of A. trifoliata wild germplasm resources and the selection of new varieties.